Peran Guru dalam Mengatasi Kesulitan Pembelajaran Matematika - Shinta Putri Andini; Muhammad Zakki (Pendidikan Matematika FKIP Universitas Mataram, 2024)
The aims of this research are: to describe teachers' efforts to overcome mathematics learning difficulties, the use of learning media to overcome mathematics learning difficulties, to describe the challenges experienced by teachers in efforts to overcome mathematics learning difficulties. This research is a library study method. The results of this research show that overcoming difficulties in learning mathematics can be done in several ways, namely: changing learning models that can attract students' interest in learning, using interesting learning media according to the learning material, involving students in using learning media, giving students freedom to ask questions about the material. what is not yet understood; and providing remedial for students who get scores below the KKM. The obstacles felt by teachers are: the amount of media is not proportional to the number of students, so that many students cannot use media during learning; the condition of many mathematics learning media that are no longer used; students find it difficult to use mathematics learning media. The teacher's role is to really help students overcome difficulties in learning mathematics. The difference between this research and previous research is that previous research discussed barriers to mathematics learning while this research discusses the role of teachers in overcoming these barriers.